Adenocarcinoma of the stomach and Fanconi's anaemia. Issue 668 (June 1981) - Hill, L. S.; Dennis, P. M.; Fairham, S. A.
Abstract : A case of Fanconi's anaemia is described. The patient developed gastric ulcers at 14 years and died of adenocarcinoma of the stomach at the age of 21 years. The need fully to investigate gastric pathology by endoscopy and biopsy, as well as radiology, is stressed. So far as the authors are aware this is the first description of adenocarcinoma of the stomach occurring in Fanconi's anaemia, a condition known to predispose to malignancy.